Desenvolvimento e perspectivas da educação estatística : narrativas de educadores estatísticos no contexto Ibero-Americano - Ody, Magnus Cesar (2019)
This research presents a study in the area of Statistical Education. The objective is to analyze the ways of seeing and conceiving its development in the origins, purposes and perspectives, especially in Brazil. The qualitative approach and the biographical-narrative investigation were used as theoretical and methodological framework. Contributions emerged from the materials produced in three moments. The first consisted of producing a historical narrative about statistics and statistical education. The second shows contemporary development, with reports produced from interviews with 15 relevant teachers in the promotion of statistical education from three Ibero-American countries: Brazil, Portugal and Spain. Facts related to the trajectories of professional formation reflected in theirs personality were observed. The third moment was the realization of narrative analysis, anchored in an illustrative, restorative and analytical framework. These, represented by the textualization of the interviews in their entirety and the construction of the narrative turn, as a way of understanding and reconstructing meanings. Historical contributions have been found to meet the development of statistical education, led by people and institutions, especially after the second half of the twentieth century. The ways of seeing and conceiving statistical education define the actions of educators in its development and show, in Brazil, a perspective of positive influence in the Ibero-American context. The collaboration of Brazilian teachers in study groups and events in the area places Brazil on the international scene. A reference due to its significant production, occupying the world second position in the elaboration of theses in statistical education. The working group on statistical education, GT12, linked to the Brazilian Society of Mathematical Education, is collaborative and active, bringing together Brazilian research groups, incorporating new members and increasing scientific production. The narratives produced reveal the professional and personal ties as a way of approaching the countries mentioned above. Statistical education is defined as an autonomous area, with a defined field of research, more strongly consolidated in the international context. In interviews, the relevance of the didactic and pedagogical interfaces of statistical education and mathematics education predominates. Defense occurs in the promotion of statistical education for all. In formal spaces, in a didactic and interdisciplinary way, with the encouragement of changes in initial and continuing education. In non-formal contexts, the opportunity and support in developing citizens' statistical and probabilistic literacy.